Talking more clearly about Europe: Why European decision-makers must improve their communication - Christian Rauh (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
Controversial public debates put pressure on the European Union to explain itself. According to various recent studies, however, the public messages of European decision-makers mostly fail to offer an adequate response: political communication by and about the EU is difficult to understand for citizens and often tends to obfuscate matters rather than to make them clear. In the current political climate, this is risky, if not dangerous. At best, unclear communication is a wasted opportunity to demonstrate the added value of political cooperation across national borders. At worst, it undermines public support for European unification.
Keywords: 300